The Costumer Care Affects Costumer Retention Through Service Quality and Customer Satisfaction - Halisu, La; Sahabuddin, Romansyah; Musa, Chalid Imran; Karim, Abdul (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
This study aims to: 1) examine the effect of customer care on service quality at a four-star hotel in Makassar; 2) see the effect of customer care on customer satisfaction; 3) see the effect of customer care on customer retention; 4) see the effect of customer care on customer retention through service quality: 5) see the effect of customer care on customer retention through customer satisfaction; 6) Service quality affects customer satisfaction; 7) Service quality has an effect on customer retention; 8) Service quality has an effect on customer retention through customer satisfaction and 9) Customer satisfaction has an effect on customer retention.